Exploring Factors Influencing Azerbaijani Public High School Students’ Choice of Major - Mirzayeva, Nigar; Jamalova Gasimova, Nigar (ADA University, 2024)
High school is a critical time for career planning since it allows students to assess their strengths, weaknesses, and the abilities they will need to succeed in the future. This study examines the factors influencing Azerbaijani public high school students' choice of major and assesses the assistance that schools offer throughout this process. The study shows how socioeconomic status, cultural influences, and family relationships all have a big influence on students' job decisions. To provide a thorough knowledge of these variables and the efficacy of current career advising strategies, this study uses qualitative methodologies, including interviews with students, parents, teachers, and administrative staff. The results are categorized into several important areas. Employability concerns, personal interests, family influence, external factors like peer recommendations and societal trends, guidance from teachers and school administration, academic achievements, economic considerations like tuition fees, and subliminal gender stereotypes are the main factors influencing major choice. These results will provide educators and policymakers with insightful information to improve career planning techniques, which will ultimately help students' abilities better match the demands of the job market, promoting both personal and economic fulfillment.
Keywords: Career development -- Azerbaijan -- Case studies; High school students -- Career choice -- Azerbaijan; Vocational guidance -- Azerbaijan; Socioeconomic status -- Azerbaijan; Azerbaijan -- Social conditions -- 21st century; Education